Crossover frequencies in spermatocytes of Robertsonian homozygotes and heterozygotes of Mus musculus domesticus - Eliana Ayarza; Marisel González; Jesús Page; Soledad Berríos (Genetics and Molecular Biology)
Abstract Crossovers (COs) generate genetic diversity and proper homologous chromosome segregation during meiosis. Mus musculus domesticus, with a diploid number of 2n=40, has 19 autosomal pairs plus one sex chromosome pair all of which are telocentric chromosomes. Frequently exhibits Robertsonian fusions (Rb), which create natural populations with reduced chromosome numbers according to the Rb chromosomes. We examined the number and distribution of COs in spermatocytes from standard homozygous 2n=40 individuals, compared to homozygous Rb 2n=24 and heterozygous Rb 2n=32 individuals carrying 8 trivalents. Spermatocyte nuclear spreads from homozygous and heterozygous were prepared, and immunocytochemistry was used to detect the MLH1 protein for crossover (CO) and the SYCP3 protein for synaptonemal complexes in bivalents or trivalents. We observed an average of 26 ± 2.1 COs in 2n=40, 20.1 ± 1.6 COs in 2n=24, and an intermediate value of 22.4 ± 2.0 COs in 2n=32 spermatocytes. The lower frequency of COs in 2n=24 and 2n=32 spermatocytes compared to 2n=40 may be due to interference from the pericentromeric heterochromatin present in the Rb bivalent or trivalent chromosomes. Additionally, we suggest that the spatial positioning and interactions of these derivative chromosomes in the nucleus could help explain the differences in COs between 2n=24, 2n=32, and 2n=40 spermatocytes.